1993
DOI: 10.1017/s000335610002122x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic insulin responses to exogenous glucose in Friesian heifers of low or high genetic merit for milk-fat yield

Abstract: Two studies were conducted to examine the effects of selection for milk-fat yield on pancreatic responses to exogenous glucose, as measured by circulating insulin concentrations following an intravenous glucose load, in heifer calves. The first study involved 6-month-old Friesian heifers, eight each from the Massey University high breeding index (HBI) and low breeding index (LBI) lines. Average breeding indices (BI) for milk-fat yield of the calves based on ancestry BI were 136 (s.d. 2) and 112 (s.d. 2), respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Blair et al (1990) and Baker et al (1990) suggested that metabolic or physiological phenotypes could be used as indirect predictors of genetic merit to significantly improve rates of genetic gain. However, despite significant research effort (see for example, Blair & Lee 1997;Xing et al 1993;Blair et al 2002), none of these types of measures have been applied in any livestock industry in New Zealand. Recently, Primegro™ have begun offering a test for plasma levels of insulin-like growth factor-1 (IGF-1) to Australian beef cattle and pig breeders (www.primegro.com.au/html/fr_primeg-ro_igf.htm).…”
Section: Selection Differentialmentioning
confidence: 99%
“…Blair et al (1990) and Baker et al (1990) suggested that metabolic or physiological phenotypes could be used as indirect predictors of genetic merit to significantly improve rates of genetic gain. However, despite significant research effort (see for example, Blair & Lee 1997;Xing et al 1993;Blair et al 2002), none of these types of measures have been applied in any livestock industry in New Zealand. Recently, Primegro™ have begun offering a test for plasma levels of insulin-like growth factor-1 (IGF-1) to Australian beef cattle and pig breeders (www.primegro.com.au/html/fr_primeg-ro_igf.htm).…”
Section: Selection Differentialmentioning
confidence: 99%
“…The insulin responses to exogenous glucose in the animals from a high breeding index line were much stronger than those of the animals from a low breeding index line 24 . Mackenzie et al 7 reported that during the challenges of both glucose and insulin, the clearance of blood glucose was most rapid in the calves with a high breeding index than in those with a low breeding index.…”
Section: Discussionmentioning
confidence: 72%
“…The sensitivity of the peripheral tissues to insulin was higher in the calves with a high breeding index than in those with a low breeding index. Therefore, the insulin response to an exogenous glucose load can be used as a metabolic marker to measure the genetic merit of milk production 24 . Glucose showed a highly positive genetic correlation with milk yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…X ing et al (1993) found that plasma insulin concentrations after glucose challenge were significantly greater in high‐index heifers than in low‐breeding‐index animals. L ukes et al (1989) investigated bGH, insulin, prolactin, FFA, and glucose plasma levels in Holstein cows of differing genetic merit after administration of either adrenaline or bGH releasing factor.…”
Section: Introductionmentioning
confidence: 91%